Chromatin clues to the trypanosome parasite's uniform coat. (1st November 2018) - Kelly, Steve; Carrington, Mark
The parasiteTrypanosoma brucei causes sleeping sickness. It evades human defences by changing the version of a protein that coats its surface. Analysis of its genome and nuclear structure clarifies this variation process. Histone proteins affect the process of antigenic variation in trypanosomes.